2012
DOI: 10.1186/1744-859x-11-1
|View full text |Cite
|
Sign up to set email alerts
|

Remission in schizophrenia: results of cross-sectional with 6-month follow-up period and 1-year observational therapeutic studies in an outpatient population

Abstract: BackgroundA standardized definition of remission criteria in schizophrenia was proposed by the International group of NC Andreasen in 2005 (low symptom threshold for the eight core Positive and Negative Syndrome Scale (PANSS) symptoms for at least 6 consecutive months).MethodsA cross-sectional study of remission rate, using a 6-month follow-up to assess symptomatic stability, was conducted in two healthcare districts (first and second) of an outpatient psychiatric service in Moscow. The key inclusion criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Second, co-morbid psychiatric conditions are common in ASD (Hofvander et al, 2009; Joshi et al, 2013; Russell et al, 2005, 2015) and symptoms of ASD are often difficult to disentangle from additional or alternative conditions (Mazzone et al, 2012; Rydén and Bejerot, 2008). This may lead to inaccurate diagnoses (Attwood, 2007) or misguided referrals to specialist clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Second, co-morbid psychiatric conditions are common in ASD (Hofvander et al, 2009; Joshi et al, 2013; Russell et al, 2005, 2015) and symptoms of ASD are often difficult to disentangle from additional or alternative conditions (Mazzone et al, 2012; Rydén and Bejerot, 2008). This may lead to inaccurate diagnoses (Attwood, 2007) or misguided referrals to specialist clinics.…”
Section: Introductionmentioning
confidence: 99%
“…1 , 2 Most family intervention programs include cognitive therapy techniques and psychoeducation. Psychoeducation promotes the development of the coping abilities of the patients and caregivers by providing information about treatment and care of the mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…While using IRC as a treatment efficacy measure, it was found out that after switching to RLAI, three times more patients achieved remission (19%) in comparison to the control group continuing routine therapy (5.7%) 25. The correlation, ANCOVA and regression analyses demonstrated that, first, a lower PANSS total score (status severity) and more favorable diagnosis, according to the ICD10, are associated with a higher probability of remission.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the authors insisted on including the item “lack of judgment and insight” (G12), showing interplay between cognitive impairment and adequate patient self-judgment and self-control. Other studies showed a close relationship between cognitive deficit and the stability of remission 17,20,25. A number of authors indicated that the IRC were mainly nonspecific and hardly differed from the psychosis global severity assessment of the Clinical Global Impression-Schizophrenia scale, which determined remission as a “not more than mild” level of psychotic intensity 16,18,36.…”
Section: Introductionmentioning
confidence: 99%